Effects of Body Weight Control Behaviors on Bone Mineral Density in Korean Young Adult Women - Chae Weon Chung; Suk Jeong Lee (Korean Society of Women Health Nursing, 2013)
PURPOSE: This study identified the effects of body weight control behaviors on bone mineral density (BMD) in Korean women aged 20 to 39 years. METHODS: A secondary analysis of the 5th Korean National Health and Nutrition Examination Survey was conducted. Asian-Pacific criteria of BMI (Body Mass Index) and BMD were calculated for 1,026 women selected. The effects of body weight control behaviors were assessed using binary multiple logistic regression analysis while controlling for BMI. RESULTS: Osteopenia and osteoporosis rates were 32.8% and 2.0%, respectively. About 69% of women performed weight control behaviors, and a combination of diet/exercise (22.7%) and drug added methods (10.9%) for weight control. Women who performed both diet control and exercise had a lower possibility to have abnormal BMD than those who did not try weight control (OR=0.67, CI=0.45~0.98, p=.039). Further weight control behaviors did not influence abnormal BMD. CONCLUSION: Body weight control should include proper diet and exercise in accordance with each woman's BMI level.